Effects of Short Practice of Climbing on Barriers Self-Efficacy within a Physical Education and Sport Intervention in Germany - Mirko Krüger; Christiane Seng (MDPI AG, 2019)
The study examined the effects of an indoor wall climbing intervention within the context of a regular Physical Education and Sport (PES) program on barriers self-efficacy (SE) of adolescents in Germany. The study used a field experiment with a wait-list control group. Seventy-eight 8th-graders were included (age: 14.41 ± 0.71 years), with 37 randomly assigned for the intervention group and 41 for the control group. The intervention group participated in two half-day indoor wall climbing excursions (duration: 180 min each) based on SE building strategies. Both groups were pre-and post-tested in SE of indoor wall climbing and belaying. The control group did not receive any treatment before post-test. After the intervention, significant improvements were found in the experimental group on SE of belaying (F(1,76) = 23.45, p = 0.000, η2p = 0.24) using repeated-measures ANOVA. This study provides the first evidence from a German PES field experiment on increasing an important SE facet related to indoor wall climbing among 8th-graders. The program may be improved and further analyzed to install a short-term method to achieve one important educational goal within ordinary PES programs in Germany and to contribute to the personal development of the students.